Multiple ontologies of water: Politics, conflict and implications for governance - Julian S Yates; Leila M Harris; Nicole J Wilson (Environment and Planning D: Society and Space, 2017)
Journal article from Environment and Planning D: Society and Space on understanding human-water relations within current water governance. The article focuses on the potential of encompassing multiple water ontologies within water governance with examples from British Columbia, Canada. We ask what it would mean to take seriously the possibility of multiple water ontologies, and what the implications of this would be for water governance in theory and practice. We contribute to a growing body of literature that is reformulating understanding of human–water relations and refocusing on the fundamental question of what water ‘is’. Interrogating the political–ontological ‘problem space’ of water governance, we explore a series of ontological disjunctures that persist. Rather than seeking to characterize any individual ontology, we focus on the limitations of silencing diverse ontologies, and on the potential of embracing ontological plurality in water governance. Exploring these ideas in relation to examples from the Canadian province of British Columbia, we develop the notion of ontological conjunctures, which is based on networked dialogue among multiple water ontologies and which points to forms of water governance that begin to embrace such a dialogue. We highlight water as siwlkw and the processual concept of En’owkin as examples of this approach, emphasizing the significance of cross-pollinating scholarship across debates on water and multiple ontologies.